Bronchodilator effect of hydroalcoholic extract of propolis from Apis mellifera "bee" in isolated tracheal rings from Cavia porcellus “guinea pigs” - Carhuapoma, Mario (2017)
The present work was carried out in order to determine the effect of bronchodilator of hydroalcoholic extract of propolis from Apis mellifera "bee" in tracheal rings isolated from Cavia porcellus "cobayos". The sample was collected in Chalhuanca district, Aymaraes province Apurímac region. Were determinated organoleptic and physical-chemical characteristics of raw propolis, and was realized phytochemical screening of hydroalcoholic extract. The bronchodilator effect was determined by the method of Jagdish et al. modified in tracheal rings, using an automated kymograph, Panlab Harvard; contractions were induced by histamine 5 x 10-4 M, registering increasing tension, number and height of contractions. It was used as control salbutamol and assessed the hydroalcoholic extract of propolis to concentrations of 5%, 10% and 15%. The hydroalcoholic extract of propolis 5% reduced tension to 10,818 g similar to salbutamol (10,852 g), getting better results to 10% and 15%, 10,206 g and 9,371 g, respectively. The number and height of contractions were 21,40 and 9,52 mm with salbutamol; 19,20 and 9,24 mm at 5%; 15,40 and 8,42 mm at 10% and finally 9,80 and 7,30 mm at 15%. Statistical analysis showed significant differences in the different treatments (p<0,05%). Was conclude that the hydroalcoholic extract of propolis has bronchodilator effect, showing greater effect at 5%.